Pathogenesis and complications of chronic eye rubbing in ocular allergy. Issue 5 (October 2019) - Ben-Eli, Hadas; Erdinest, Nir; Solomon, Abraham
Abstract : Purpose of review: To review the updated literature regarding eye rubbing complications and its association with ocular allergy disorders. Recent findings: Atopy and ocular allergy disorders, mainly vernal keratoconjunctivitis (VKC), are strongly associated with rubbing-related complications, most probably via itching and watery eye sensations that trigger the habit of chronic eye rubbing. Vigorous and prolonged rubbing may lead to establishment of corneal remodeling and ectatic disorders, such as keratoconus. Keratoconus development in rubbed eyes can be caused by mechanical mechanisms of corneal thinning and its loss of rigidity, by elevated temperature of the epithelium during rubbing, by increased intraocular pressure (IOP) because of distending forces, and by inflammatory molecules that may serve as a causal mediator between eye rubbing and keratoconus. Other eye rubbing complications include acute hydrops and perforation, IOP spikes, iris prolapse and iridoschisis rupture of lens capsule and IOL dislocation, and even posterior segment disorders, such as glaucomatous optic neuropathy, retinal detachment and extrusion of implanted silicone oil in the eye. Summary: Chronic eye rubbing in allergic eye diseases can lead to progression of keratoconus, and to other rare anterior and posterior segment complications. Strategies eliminating eye rubbing and its consequences are vital, mainly among at-risk populations, such as young children and individuals with allergic ocular disorders or corneal transplants.